Peningkatan Kualitas Pembelajaran melalui Media Pembelajaran LCD Proyektor bagi Guru dan Siswa KB Bina Cendikia Desa Sidorejo Kecamatan Jabung Kabupaten Malang - Muhammad Akhlis Rizza; Zakki Fuadi Emzain; Ratna Monasari; Etik Puspitasari (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
The use of technology continues to penetrate various aspects of life, one of which is the utilization of technology in the field of education at the Playgroup Level (KB). At KB Bina Cendikia in Jabung Subdistrict, Malang has not used technology for learning media such as LCD projectors; therefore, there is necessary to teach media by utilizing this technology to increase learning activities. This community service activity (PPM) aims to provide learning media in the form of an LCD projector and its equipment and to train KB Bina Cendikia teachers to operate and maintain it. The PPM activities stages include surveys, coordination, procurement, socialization, and handovers. The results of the PPM activity showed that the thematic learning process at KB Bina Cendikia using LCD projector media could make students happier. It demonstrated the students' enthusiasm for participating in the lessons, and there was also an increase in learning activities. KB teacher Bina Cendikia also responded positively to using LCD projectors in thematic learning.